2021
DOI: 10.3390/polym14010061
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strength, Elastic Modulus and Remineralizing Abilities of Bioactive Resin-Based Dental Sealants

Abstract: Objective: To assess the remineralizing abilities and compare the flexural strength and elastic modulus of different bioactive pit and fissure sealants. Materials and Methods: Human enamel samples were randomly and blindly sealed with one of the following bioactive materials: BioCoat (Bc), ACTIVA KIDS (Av) and BeautiSealant (Bu). Seal-it (Si) was used as a non-bioactive sealant beside a control blank (B) group with no sealant. The sealed samples were subjected to a pH-cycling model (7 days of demineralization–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 46 publications
(71 reference statements)
4
8
0
Order By: Relevance
“…A recent study investigated the flexural strength, elastic modulus, and remineralization abilities after 7 days of pH-cycling of bioactive and non-bioactive sealant materials and found that BioCoat TM had the highest amount of fluoride, calcium, and phosphate ions, and the tinniest demineralization area; moreover, they were also superior in terms of their flexural strength and modulus of elasticity [24]. This supports choosing BioCoat TM as the material representing Bio-RBS in this study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A recent study investigated the flexural strength, elastic modulus, and remineralization abilities after 7 days of pH-cycling of bioactive and non-bioactive sealant materials and found that BioCoat TM had the highest amount of fluoride, calcium, and phosphate ions, and the tinniest demineralization area; moreover, they were also superior in terms of their flexural strength and modulus of elasticity [24]. This supports choosing BioCoat TM as the material representing Bio-RBS in this study.…”
Section: Discussionsupporting
confidence: 75%
“…The company claims that the material releases ionic fluoride, calcium, and phosphate and that it has a similar retention to other RBS [23]. A recent study compared this material to other bioactive materials and found BioCoat TM to have the highest flexural strength, elastic modulus, and remineralization abilities [24]. Another study found inhibition of enamel demineralization with experimental sealants containing bioactive glass in a cariogenic environment and concluded that PFS containing a bioglass filler is a promising dental material to prevent marginal or secondary caries at the marginal gap [25].…”
Section: Introductionmentioning
confidence: 99%
“…When demineralization took place, this led to the influx of the fluoride, calcium and phosphate ions to the demineralized enamel promoting its remineralization. Calcium and phosphate potentiated the action of fluoride giving the obtained results of group 1 (3) .…”
Section: Resultsmentioning
confidence: 66%
“…The results of group 3 Helioseal Clear non-fluoride releasing resin-based sealant are displayed in figure (3). These observations can be attributed to the lack of any anticarious ions as fluoride that can inhibit the demineralizing circumstances of the current study (4) .…”
Section: Resultsmentioning
confidence: 66%
“…Sample size was calculated using G*power sample size calculator program (3.1.9.6) for Mac. At power equal 95%, α equal 0.05 and effect size (2.1) based on the anticipated mean values of mineral released from the two bioactive sealants according to Fita k et.al (19) and Ibrahim MS et.al (20) . Statistical t test for the difference between two independent means of two groups calculation was used, and the minimal total sample size was (12 teeth), which was increased to (32 teeth) to increase the statistical power.…”
Section: Sample Size Calculationmentioning
confidence: 99%